2023
DOI: 10.3390/ijms24032706
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Coffee Consumption for Cancer and Other Diseases and Mechanisms of Action

Abstract: Coffee is one of the most widely consumed beverages worldwide, and epidemiology studies associate higher coffee consumption with decreased rates of mortality and decreased rates of neurological and metabolic diseases, including Parkinson’s disease and type 2 diabetes. In addition, there is also evidence that higher coffee consumption is associated with lower rates of colon and rectal cancer, as well as breast, endometrial, and other cancers, although for some of these cancers, the results are conflicting. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 182 publications
0
6
0
Order By: Relevance
“…The mechanisms that underlie the potential benefits of coffee consumption on CRC recurrence are yet to be fully elucidated. However, coffee consumption has been proposed to be protective against the hallmarks of cancer 16 by activating pathways such as nuclear factor erythroid 2(Nrf2)‐regulated pathways that reduce oxidative stress 39 . Coffee consumption could also modulate microbiota composition which in turn may promote the chemopreventive or chemotherapeutic actions against CRC 20,40–42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms that underlie the potential benefits of coffee consumption on CRC recurrence are yet to be fully elucidated. However, coffee consumption has been proposed to be protective against the hallmarks of cancer 16 by activating pathways such as nuclear factor erythroid 2(Nrf2)‐regulated pathways that reduce oxidative stress 39 . Coffee consumption could also modulate microbiota composition which in turn may promote the chemopreventive or chemotherapeutic actions against CRC 20,40–42 .…”
Section: Discussionmentioning
confidence: 99%
“…However, coffee consumption has been proposed to be protective against the hallmarks of cancer 16 by activating pathways such as nuclear factor erythroid 2(Nrf2)-regulated pathways that reduce oxidative stress. 39 Coffee consumption could also modulate microbiota composition which in turn may promote the chemopreventive or chemotherapeutic actions against CRC. 20,[40][41][42] Coffee consumption may also prevent metastatic growth of CRC by improving the function of the liver in CRC patients 43 and by protecting against non-alcoholic fatty liver disease, 44 which is considered a risk factor for liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of cancer may be reduced in subjects consuming coffee, but this needs further investigation. Within the components of coffee, caffeine, chlorogenic acids, polyphenols, alkaloids, vitamins, metals, and terpenoids can be specified [ 73 , 74 ]. In the literature, studies revealing the effects of coffee use in NAFLD patients can be found.…”
Section: A Brief Description Of the Substances And Their Usefulness I...mentioning
confidence: 99%
“…Coffee is a widely consumed beverage rich in bioactive compounds with positive impacts on health, including the reduction of incidence of Parkinson disease, Alzheimer disease, certain types of cancer, type 2 diabetes, and obesity (Carneiro et al, 2021; Corbi‐Cobo‐Losey et al, 2023; Safe et al, 2023). In a large prospective study, Liu et al (2022) found that coffee consumption reduced the risk of death from various causes.…”
Section: Introductionmentioning
confidence: 99%